2021
DOI: 10.1021/acs.jcim.0c01353
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Molecular Inhibition of the Oncogenic Channel KV10.1 by Globular Toxins

Abstract: Inhibition of the expression of the human ether-a-go-go (hEAG1 or hK V 10.1) channel is associated with a dramatic reduction in the growth of several cancerous tumors. The modulation of this channel's activity is a promising target for the development of new anticancer drugs. Although some small molecules have shown inhibitory activity against K V 10.1, their lack of specificity has prevented their use in humans. In vitro studies have recently identified a limited number of peptide toxins with proven specifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…techniques. The results obtained have shown that APETx4 is endowed with multiple binding sites and its inhibitory effect is likely due to induced steric effects that prevent the contact of the extracellular loop in the channel with its voltage sensor domain, thus stabilizing the channel structure in the deep closed state [38].…”
Section: Cnidaria-antozoamentioning
confidence: 99%
See 1 more Smart Citation
“…techniques. The results obtained have shown that APETx4 is endowed with multiple binding sites and its inhibitory effect is likely due to induced steric effects that prevent the contact of the extracellular loop in the channel with its voltage sensor domain, thus stabilizing the channel structure in the deep closed state [38].…”
Section: Cnidaria-antozoamentioning
confidence: 99%
“…More recent studies have been directed to reveal the APETx4–K V 10.1 interactions in an atomic resolution, using protein docking and multiscale molecular dynamics techniques. The results obtained have shown that APETx4 is endowed with multiple binding sites and its inhibitory effect is likely due to induced steric effects that prevent the contact of the extracellular loop in the channel with its voltage sensor domain, thus stabilizing the channel structure in the deep closed state [ 38 ].…”
Section: Marine Animals As Sources Of Anticancer Peptides: In Vitro E...mentioning
confidence: 99%